Reading Comprehension and Cognitive Processes in Ecuadorian Middle School Students - Barberán, Sandra Ximena; Mendoza Mejia, Jorge Luis; Torrealba Peña, Mairelys Jaciel; Vásconez Rivera, Indira Nataly; Hurtado Guevara, Richard Fernando (Journal of Ecohumanism, 2024)
Objective: The research aimed to determine the influence of reading comprehension on the development of cognitive processes in middle school students in the canton of El Carmen. Methodology: It was based on the positivist paradigm through a quantitative approach with a correlational field research. The study population consisted of 983 teachers belonging to the ten educational circuits that make up the canton, applying a survey through a polytomous questionnaire with a Likert scale. Results and Discussion: Among the most relevant results, it is evident that there is a moderate correlation calculated at 0.457, which establishes that reading comprehension influences the development of cognitive processes in middle school students. Conclusion: It is of utmost importance that teachers working in the educational institutions under study not only develop their classes through the execution of curricular content but also employ strategies that allow students to learn to learn, which is achieved by stimulating the cognitive system.